Estudo de correlações entre os ensaios de penetração estática e dinâmica e suas aplicações ao projeto de fundações profundas - Danziger, Bernadete Ragoni (1982)
The ever present interest in applying field tests to determine the bearing capacity of foundations, particularly deep foundations, explains the necessity to check, or modify, existing correlations between the "standard penetration test" and the "diepsondering". Considerations are made concerning the statistical approach to the problem and comparisons are made between the results obtained here with values reported in the literature, as well as suggestions are made with respect to the application of correlations. Load tests on different pile types are analysed and compared to the results of the usual methods of prediction of the ultimate pile load. The variations found in such comparisons are believed to be due more to the rough character of the borings rather than to the quality of the correlation or to the accuracy of the method of calculation. The question of the philosophy of foundations projects is also dealt with and suggestions are made concerning the application of the correlations as well as its continuous appropriateness as a means of evaluating the store of experience acquired with its utilization in engineering practice.